Efficacy and safety of an antiviral Iota-Carrageenan nasal spray: a randomized, double-blind, placebo-controlled exploratory study in volunteers with early symptoms of the common cold - Eccles, Ron (BioMed Central, 2010)
BACKGROUND: The common cold, the most prevalent contagious viral disease in humans still lacks a safe and effective antiviral treatment. Iota-Carrageenan is broadly active against respiratory viruses in-vitro and has an excellent safety profile. This study investigated the efficacy and safety of an Iota-Carrageenan nasal spray in patients with common cold symptoms. METHODS: In a randomized, double-blind, placebo-controlled exploratory trial, 35 human subjects suffering from early symptoms of common cold received Iota-Carrageenan (0.12%) in a saline solution three times daily for 4 days, compared to placebo. RESULTS: Administration of Iota-Carrageenan nasal spray reduced the symptoms of common cold (p = 0.046) and the viral load in nasal lavages (p = 0.009) in patients with early symptoms of common cold. Pro-inflammatory mediators FGF-2, Fractalkine, GRO, G-CSF, IL-8, IL-1α, IP-10, IL-10, and IFN-α2 were reduced in the Iota-Carrageenan group. CONCLUSIONS: Iota-Carrageenan nasal spray appears to be a promising treatment for safe and effective treatment of early symptoms of common cold. Larger trials are indicated to confirm the results.